"What we owe our children, they their children, and..." - John Roemer (University of California, Department of Economics, 1999)
Egalitarian theorists, since Rawls, have in the main advocated equalizing some objective standard of individual well-being, such as primary goods, functioning, or resources, rather than subjective welfare. This discussion, however, has assumed, implicitly, a static environment, with a single or perhaps a small number of generations. By studying the problem of equality of opportunity in a society that survives for many generations, we demonstrate that equality of opportunity for some objective condition of individuals is incompatible with a natural notion of human development over time. We argue that this incompatibility can be resolved by equalizing opportunities for welfare. Thus, â??subjectivismâ?? seems necessary if we are to hope for a society which can both equalize opportunities and support the development of human capacity over time.
Keywords: 330